1996
DOI: 10.1159/000159170
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Acetylcholine-lnduced Responses in Freshly Isolated Rabbit Aortic Endothelial Cells

Abstract: Acetylcholine (ACh)-induced membrane hyperpolarization was studied in freshly isolated endothelial cells from rabbit aorta. Ten µM ACh induced transient hyperpolarization due to the opening of Ca2+-sensitive K+ channels, sensitive to TEA and charybdotoxin (CTX). The membrane potential response was accompanied by an increase in intracellular Ca2+ [Ca2+]i. Pretreatment of endothelial cells with 20 µM ATP, 0.2 µM bradykinin or 0.1 µM platelet-aggregating fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
1
18
1
Order By: Relevance
“…[23][24][25] These large E m changes to SP and BK clearly contrast with the very slight hyperpolarizing responses to these peptides that we observed in current-clamped intact endothelial cells. They also contrast with the findings of Wang et al 19 in freshly isolated current-clamped endothelial cells of rat aorta studied by the perforated-patch method. In this endothelial preparation, BK (400 nmol/L) also elicited only a slight hyperpolarizing response, whereas ACH (10 mol/L) induced pronounced hyperpolarizations averaging 51 mV in the intact endothelial cells.…”
Section: Hyperpolarizing Responses To Sp and Bk Differ Between Culturcontrasting
confidence: 93%
See 2 more Smart Citations
“…[23][24][25] These large E m changes to SP and BK clearly contrast with the very slight hyperpolarizing responses to these peptides that we observed in current-clamped intact endothelial cells. They also contrast with the findings of Wang et al 19 in freshly isolated current-clamped endothelial cells of rat aorta studied by the perforated-patch method. In this endothelial preparation, BK (400 nmol/L) also elicited only a slight hyperpolarizing response, whereas ACH (10 mol/L) induced pronounced hyperpolarizations averaging 51 mV in the intact endothelial cells.…”
Section: Hyperpolarizing Responses To Sp and Bk Differ Between Culturcontrasting
confidence: 93%
“…10,16 -19 This hyperpolarizing response has been linked to the elevation of cytosolic Ca 2ϩ levels in the endothelial cell and appears to be obligatory for the release of dilator factors. 12,18,19 For example, in bioassay experiments of rabbit aorta, Demirel et al 10 have shown that perfusion of ACH through endothelium-intact donor rings results in the relaxation of recipient rings denuded of endothelium. In this preparation, pharmacological block of K ϩ channels in the ACH-stimulated donor segment inhibited the downstream relaxation of the recipient ring, inferring that ACH activates endothelial K ϩ channels to mediate the release of dilator factors.…”
Section: Discussion Endothelial Cell Hyperpolarizing Responses To Achmentioning
confidence: 99%
See 1 more Smart Citation
“…Rearrangement of the microfilamentous cytoskeleton represents a potential mechanism underlying SOCE-induced shape change in endothelial cells (Moore et al 1998). Other studies have shown the involvement of calcium/calmodulin-dependent protein kinase II (d) in endothelial barrier dysfunction ) and indicated its influence on cytoskeletal organisation by affecting translocation of filamin (Wang et al 1996) and stress fiber formation (Borbiev et al 2003). In pulmonary arteries, involvement of the potential SOCE channel proteins TRPC1 and TRPC4 in inflammation-associated loss of endothelial barrier function has been suggested.…”
Section: Soce In the Endothelial Inflammatory Responsementioning
confidence: 99%
“…The cells were passaged with trypsin-EDTA (Life Sciences, St. Petersburg, FL) and maintained in a humidified atmosphere of 5% CO 2 at 37°C. Rabbit aortic endothelial cells (RAECs) were prepared from freshly sacrificed rabbits as described (Wang et al, 1996).…”
Section: Endothelial Cell Culturementioning
confidence: 99%